Analysis of network of biserial queues linked with a common server. (1st January 2014) - Sharma, Seema; Gupta, Deepak; Sharma, Sameer
This paper is an attempt to study the steady state analysis of a complex network of queues in which a common server is linked in series with each of two parallel biserial servers. The arrival and service pattern follows Poisson law. The generating function technique, law of calculus and statistical tools have been used to find the various queue characteristics. The model finds its application in decision making, in process industry, in banking system, in communication networking, in supermarkets, in healthcare centre and in many administrative setups. An algorithm is proposed to find the mean queue length of customers/jobs, variance of queues and average waiting time of customers/jobs. The performance of algorithm is assessed by a numerical illustration.